Peranan Camat Dalam Mewujudkan Good Governance di Kecamatan Tombatu Kabupaten Minahasa Tenggara - TULANDI, NICKY; Rompas, Sonny; Pombengi, Jericho (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: Camat position as a leader in the district and at the same time as the head of the workingarea districts have an important role and ultimately determine the manifest good govenance in thedistrict, but in fact good govenance not been optimally realized in the district. This study intended tofind out how camat role in achieving good Governace in the district of Minahasa district Tombatusoutheast.The research method used is qualitative method. camat role in achieving good governance fi viewof three aspects, namely pernan coordinate, direct, and supervise government in the district.informants in this study as many as 15 people were taken from the element of government officials,elements of SKPD and vertical institutions in the district, the village government elements, andorganisa civic or community leaders. a key instrument in this study is the researchers themselves, whilecollecting data using interview techniques. Data analysis was performed using analysis modelsinterkatif qualitave analysis of miles and hubernann. The results of data analysis that addressed therole camat coordinate, direct and supervise activities in the district administration to achieve goodgovernance is done properly and effectively in Kecamtan Tombatu.Based on the research results deduced that camat the position / positions, duties andauthorities coordinate, direct and supervise the government penyelenggraan in districts having acrucial role in achieving good governance.Departed from the conclusions of the study put forward suggestions: camat must optimizethe use of means of organizing pemerintaha coordination of all work units pemetintah; optimizing thepotential and the ability to provide guidance to government work units in the working area districts;and optimize the existing control facilities such as reporting systems, and monitoring and evaluationsystem.Key words: the role of the subdistrict head, good governance